İŞ GÜVENLİĞİ TEFTİŞİ SULANDIRILMAMALIDIR! - (:unkn) unknown (My University, 2014)
6331 sayılı İş Sağlığı ve Güvenliği Kanunuyla birlikte iş sağlığı ve güvenliği hukuku alanında yeni bir dönem başlamıştır. Ne var ki, Çalışma ve Sosyal Güvenliği Bakanlığı tarafından hazırlanan İş Teftişi Tüzüğü ile İş Teftiş Kurulu Yönetmeliği tasarılarının iş sağlığı ve güvenliği ile işin yürütümü denetiminin aynı müfettiş tarafından yapılmasına olanak sağlaması kaygı uyandırmaktadır. Bu tasarılar, teftişi izin koşuluna bağlamakta; ayrıca iş sağlığı ve güvenliği denetimi alanında uzmanlaşmayı da engelleyerek işçilerin yaşamını tehlikeye atmaktadır.

Law No. 6331 concerning occupational health and safety has heralded a new era in the field of occupational health and safety law. Nevertheless, the regulations of labour inspection and labour inspection board drafted by the Labour and Social Security Ministry is of great concern due to the fact that they allow the social and technical inspection to be carried out by the same inspector. Moreover, these drafts bind the inspection upon the permission condition. Finally, they endanger the lives of the employees by hindering the specialisation in the field of occupational health and safety inspection.
Labour Safety Inspection Should Not Be Abused!
Keywords: Hukuk